SOME OBSERVATIONS ON THE BACKWATER CLAM, MERETRIX CASTA (CHEMNITZ) IN THE BEYPORE AND KORAPUZHA ESTUARIES - Seshappa, G (Indian Journal of Fisheries, 2011)
The backwater clam, Meretrix casta (Chemnitz), is a bivalve mollusc ofconsiderable commercial importance and occurs in estuaries and backwaters of boththe east and west coasts of India. Any biological study of this species will thereforebe of interest from the scientific and also the fisheries points of view. Beforethe 'fifties Hornell's work seems to be the only instance in the country, of any considerableinterest in this species (Hornell, 1917 and 1921) both from a systematic andthe economic points of view. In 1953 Abraham made some detailed studies oncertain aspects of the biology of the species including a study of the environmentand also the growth rate under natural as well as experimental conditions, basedon material from the Adyar waters near Madras.